Vestibular disorders in elderly people (conference proceedings) - Editorial article (LLC "MEDIAFORMAT", 2021)
The causes and clinical manifestations of vestibulopathies in elderly people are extremely diverse. The experts of CON-MED.RU, the professional information resource for healthcare specialists, the expert on gerontology Elen A. Mkhitaryan (PhD, head of the laboratory of neurogeriatrics and cognitive impairment under the Science section, Pirogov Russian National Research Medical University, Russian Clinical and Research Center of Gerontology), and one of the most recognized Russian neurologists, the expert on vertigo Maxim V. Zamergrad (D. Sci. (Med.), professor at the Department of Neurology with the course of reflexology and manual therapy, Russian Medical Academy of Continuous Professional Education), clarified this issue, which was difficult for clinicians.